1999
DOI: 10.1021/jp9843252
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics of Auramine O in Low-Viscosity Solutions as Investigated by an Ultrafast Lensing Effect

Abstract: Ultrafast change in refractive index after excitation by a femtosecond laser pulse was observed for dilute Auramine O solutions in low-viscosity solvents by detecting the change as an ultrafast lensing effect (ULE). The decay of the ULE signals was found to consist of two components, and both their relaxation times depended on solvents. This is the first reported observation of the faster component by this technique. The slower component had a similar relaxation time to that of the fluorescence lifetime. Molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 25 publications
3
32
0
1
Order By: Relevance
“…We interpreted the slower two components of the TIR-UTL signal according to the following two models: (1) The internal conversion process from the LE to the TICT-like state of AuO adsorbing on the interface corresponds to τ2 and the relaxation process from the TICT-like state to the ground state corresponds to τ3. Such a refractive-index change was also observed in highviscosity solvents 4 and in AOT reversed micelles. 14,15 (2) There are two kinds of AuO that interact differently with the interface.…”
Section: Development Of the Total-internal-reflection Ultrafast Transsupporting
confidence: 54%
“…We interpreted the slower two components of the TIR-UTL signal according to the following two models: (1) The internal conversion process from the LE to the TICT-like state of AuO adsorbing on the interface corresponds to τ2 and the relaxation process from the TICT-like state to the ground state corresponds to τ3. Such a refractive-index change was also observed in highviscosity solvents 4 and in AOT reversed micelles. 14,15 (2) There are two kinds of AuO that interact differently with the interface.…”
Section: Development Of the Total-internal-reflection Ultrafast Transsupporting
confidence: 54%
“…In more viscous environment, for instance in the presence of polymeric acids or DNA, an increase in the quantum yield and lifetime of fluorescence was observed [15,31,32]. With AO intercalated in DNA, a multi-exponential emission was observed with the longer lifetimes in the neighborhood of 1 ns [14]. This was the consequence of a decreased efficiency in the internal movements of AO, and especially of the phenyl rotation.…”
Section: Steady-state and Time-resolved Fluorescence Measurements Of mentioning
confidence: 97%
“…Then, the properties of the cores were investigated by fluorescence spectroscopy. The fluorescent molecule that was selected was the cationic probe Auramine O (AO), whose emission was sensitive to its close environment [14][15][16][17][18][19]. Being cationic, it was expected that AO could be trapped in the core of the micelle.…”
Section: Introductionmentioning
confidence: 99%
“…The first was made in 1999 by Sawada and co-workers. 42 In their study, the authors employed the ultrafast lensing effect (ULE) and found a short relaxation time component for AuO in low-viscosity solvents, which they ascribed to friction arising from hydrogen bonds rather than from polarity/dielectric relaxation. The second was a study conducted under much more extreme conditions.…”
Section: ■ Introductionmentioning
confidence: 99%